2005
DOI: 10.2174/1568005054201517
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Polyvalent Approach to HIV-1 Vaccine Development

Abstract: One major obstacle to the design of a global HIV-1 vaccine is viral diversity. Presently, data suggest that a single antigen will not suffice to generate broadly reactive neutralizing antibodies to protect all individuals against all subtypes of HIV-1 infection. While some of the neutralizing epitopes are identified in the constant regions of the HIV-1 envelope (Env) glycoprotein, many are localized to variable regions and differ conformationally from one virus to the next. The successes of polyvalent vaccine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 95 publications
1
16
0
Order By: Relevance
“…Our studies included a demonstration that successive inoculations with envelope recombinant vaccines given in the order D, V and P elicited durable B-cell and T-cell responses [22;45-47]. We also showed that multi-envelope vaccines generated superior immune breadth compared to single-envelope vaccines (as has also been demonstrated by other groups [7;48-50]), that the inclusion of a minor component in a mixed vaccine was sufficient to elicit a type-specific immune response [51], and that the grouping of envelopes by subtype or origin did not always correlate with antigenicity (as also confirmed by work in other laboratories [52;53]). Finally, we demonstrated that a multi-envelope D-V-P vaccine could protect macaques from disease following challenge with a heterologous SHIV [54].…”
Section: Reviewsupporting
confidence: 65%
“…Our studies included a demonstration that successive inoculations with envelope recombinant vaccines given in the order D, V and P elicited durable B-cell and T-cell responses [22;45-47]. We also showed that multi-envelope vaccines generated superior immune breadth compared to single-envelope vaccines (as has also been demonstrated by other groups [7;48-50]), that the inclusion of a minor component in a mixed vaccine was sufficient to elicit a type-specific immune response [51], and that the grouping of envelopes by subtype or origin did not always correlate with antigenicity (as also confirmed by work in other laboratories [52;53]). Finally, we demonstrated that a multi-envelope D-V-P vaccine could protect macaques from disease following challenge with a heterologous SHIV [54].…”
Section: Reviewsupporting
confidence: 65%
“…These data support the use of vaccine constructs that carry epitopes of divergent HIV-1 variants rather than of single strains, and they imply that polyvalent vaccination schemes may be preferable to monovalent ones. Indeed, recent vaccine studies support this hypothesis, suggesting that vaccines based on multiple strains do induce superior nAbs (11,23,(28)(29)(30). Zolla-Pazner et al demonstrated that immunization of rabbits with V3 fusion proteins from HIV-1 clades A, B, and C induces anti-HIV-1 antibodies with better potency and breadth than immunization of rabbits with V3 fusion proteins from a single clade (30).…”
Section: Discussionmentioning
confidence: 99%
“…The HIV-1 Env gp120 was conjugated to multimers of P28 and directly compared to elicitation of immune responses by Env gp120 conjugated to multimers of the full C3d protein. DNA vaccines expressing Env gp120 are poorly immunogenic when expressed from DNA, eliciting low anti-Env immunity ( Figures 3 and 4, as well as 11,12,17,20,[30][31][32] ); however, the HIV-1 envelope is highly immunogenic when presented to the immune system as a purified protein 30,[35][36][37][38][39][40][41][42][43][44][45][46][47][48] . Fusion of multimers of the whole C3d or the P28 peptide to Env gp120 enhanced the level of immunogenicity, regardless of the route of inoculation of DNA.…”
Section: Discussionmentioning
confidence: 99%